Análisis de la gestión estratégica, financiera y de marketing de la empresa Comboplay (2024)
This work aims to analyze the financial, marketing and marketing areas of the company COMBOPLAY SAS, thus identifying the information found there, since it is of vital importance for the development and growth of the organization, it is important to clarify that in the management financial we will be able to observe in more depth the management of resources, income, costs, expenses, liquidity, profitability, utility, etc., in the marketing area we present a plan that is aimed at a specific product so we can get a better idea specific about the needs that can be satisfied, and finally in the market area we make a scorecard in which each area is detailed and its strategies, description, actions and indicators will be identified.